Awareness and practices of green information technology among technology management students in Universiti Utara Malaysia - Tan, Soo Ean; Ibrahim, Jafni Azhan (2017)
Green Information Technology (Green IT), also known as green computing is applying technologies to make environmental friendly.Technology may bring certain issues harmful to us.The main issue is environmental problems such as energy consumption, pollution and e-waste.Therefore the practicing of green information technology is vital for environmental protection.There are limit resources of awareness and practices of green information technology available for universities in Malaysia.This study aims to investigate the level of awareness and practices of green information technology among university students. Then, find the gap between awareness and practices of green information technology in order to analyses the relationship of awareness and practices of green information technology.This research was conducted by using quantitative method and 175 samples of usable questionnaire forms have been collected from Technology Management student in University Utara Malaysia. The research finding was based on the factors of practices that have the relationship with green information technology awareness which are energy saving, paperless and recycling.Descriptive analyses result showed the level of green information technology awareness and practices both are in middle high rate.It can conclude that awareness of green information technology is affecting the practices of green information technology.